You Will Recognize Her… About the Transformations of the Female Body in Cinema - Regina V. Penner (Corpus Mundi, 2024)
The study of female corporality in cinema is relevant in the context of the analysis of contemporary ideas about the body as a cultural and ideological construct. In the con-text of mass visual culture, the female body is often depicted stereotypically, emphasizing either sexualized or vulnerable aspects, which limits the depth of perception of corporality and female identity. The purpose of the article is to identify how cinematic images of the female body serve as a means of conveying cultural and social meanings, as well as to expose the illusory nature of ideas about the female body often created by screen culture. The study applies methods of socio-philosophical, cultural and feminist analysis, as well as the theory of visual media. Particular attention is paid to the concept of the “male gaze” and the fragmentation of corporality, which are used to identify and deconstruct stereotypical images in cinema. One of the key results of the work was the conclusion that the female corporality on screen is often depicted as a visually attractive shell, devoid of deep meaning and authenticity. Cinema represents the body as an object of the viewer's gaze, reinforcing ideological stereotypes and turning the body itself into an instrument of manipulation. The absence of an authentic body leads to a loss of subjectivity, which creates a need for new approaches to visualizing corporeality that can bring the viewer closer to an authentic experience.